In vitro anticancer activity of N-benzyl 1,10-phenanthroline derivatives on human cancer cell lines and their selectivity - Eti Nurwening Sholikhah; Jumina Jumina; Sitarina Widyarini; Mustofa Mustofa; Ruslin Hadanu (Indonesian Journal of Biotechnology, 2018)
This research was conducted to evaluate the anticancer activity of new compounds of benzyl-1,10- phenanthroline derivatives and their selectivity. In vitro anticancer activity of 11 benzyl-1,10-phenanthroline derivatives were conducted on three human cancer cell lines, cervical cancer (HeLa), myeloma (NS-1), and breast cancer (MCF-7) using MTT-based cytotoxicity assay. The cytotoxicity of each compound was assessed to normal Vero cell line by the same method. The in vitro anticancer activity and cytotoxicity was expressed by the concentration inhibiting 50% of the cell growth (IC50), and the selectivity index (SI) was determined by calculating ratio of the IC50 on Vero cell line and the human cancer cell lines. The results showed that among the 11 compounds tested, the (1)-N-(4-butoxybenzyl)-1,10-phenanthrolinium bromide exhibited the best in vitro anticancer activity with an IC50 27.60 ± 2.76 µM on HeLa, 6.42 ± 5.53 µM on NS-1 and 9.44 ± 2.17 µM on MCF-7 cell lines. Its SI were 377.65 ± 39.97 on HeLa, 6158.72 ± 5306.34 on NS-1 and 1140.11 ± 261.85 on MCF-7 cell lines. This study demonstrated that (1)-N-(4-butoxybenzyl)-1,10-phenanthrolinium bromide possessed a potential in vitro anticancer activity on cancer cell lines with high selectivity